Dietary Habits of Senior Citizens - Ajitha R (Department of Home Science, College of Agriculture, 2000)
The study entitled "Dietary habits of senior citizens", was conducted to assess the dietary pattern of senior citizens as influenced by physical, psychological, socio- • economic factors. Two hundred elderly citizens in the age group of 65-75 years from urban (100) and rural (100) areas ofTrivandrum were selected for the study. There was major variations between rural and urban elderly as well as male and female elderly as far as their economic, social and personal profile were examined, which could influence their dietary pattern directly or indirectly. The urban citizens had better educational status than rural citizens. Though there were no major variations in the number of citizens currently employed both among urban and rural citizens, there was significant variation in their dietary habits. The meal pattern of urban citizens were relatively adequate than rural citizens. The inclusion of nutritious foods were less among rural citizens. Both urban and rural citizens had made changes in their diet due to problems related to aging. The personal habits like smoking, tobacco use, alcohol, consumption were less among urban citizens. They had also perceived their health to be good. They had better functional ability (mainly IADL), and also better physical and social environment. The female citizens had better body weight than men and the prevalence of deficiency diseases and other degenerative diseases were low among them. But male citizens were doing strenuous activity and they had better functional capacity than females. The results of the study revealed a significant association between dietary habits of the elderly and their socio-economic and personal characteristics. It was observed